The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1530/eje-13-0308
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Autocrine/paracrine regulatory mechanisms in adrenocortical neoplasms responsible for primary adrenal hypercorticism

Abstract: A wide variety of autocrine/paracrine bioactive signals are able to modulate corticosteroid secretion in the human adrenal gland. These regulatory factors, released in the vicinity of adrenocortical cells by diverse cell types comprising chromaffin cells, nerve terminals, cells of the immune system, endothelial cells, and adipocytes, include neuropeptides, biogenic amines, and cytokines. A growing body of evidence now suggests that paracrine mechanisms may also play an important role in the physiopathology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 248 publications
0
30
0
1
Order By: Relevance
“…The third steroid, 17-OHP, having an elevated response to ACTH in the carriers of c5 haplotypes, is the substrate of the steroid 21-hydroxylase enzyme and the enzyme is functionally unidirectional [1], hence the direct effect of CYP21A2 haplotypes hardly explain the elevated 17-OHP response. We hypothesize that the paracrine regulation of adrenal steroidogenesis [35], either directly or indirectly activated by higher cortisol response may the mediate elevated 17-OHP response, and, in fact, an intraadrenal positive regulatory loop exerted by cortisol is observed in some cases [36].…”
Section: Discussionmentioning
confidence: 97%
“…The third steroid, 17-OHP, having an elevated response to ACTH in the carriers of c5 haplotypes, is the substrate of the steroid 21-hydroxylase enzyme and the enzyme is functionally unidirectional [1], hence the direct effect of CYP21A2 haplotypes hardly explain the elevated 17-OHP response. We hypothesize that the paracrine regulation of adrenal steroidogenesis [35], either directly or indirectly activated by higher cortisol response may the mediate elevated 17-OHP response, and, in fact, an intraadrenal positive regulatory loop exerted by cortisol is observed in some cases [36].…”
Section: Discussionmentioning
confidence: 97%
“…Additional work indicated that PMAH tissues also produce serotonin, vasopressin, glucagon, and other factors that further contribute to the paracrine regulatory loops of cortisol secretion and cell proliferation (Lefebvre et al 2013). These findings bolster the proposal that paracrine adrenal production of ACTH is central to the cortisol-facilitated regulation of PMAH.…”
Section: Ectopic Expression Of Corticotropin In Pmahmentioning
confidence: 59%
“…Therefore, an increase in [Ca 2+ ] i is an initiator of apoptosis in V. vulnificus B2 infection. Ca 2+ regulates many signaling pathways such as protein kinase C (PKC), extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK), which can mediate apoptosis [37,38]. We found that m-Tor and STAT3 signaling pathway were involved in DC apoptosis induced by V. vulnificus B2, where m-Tor expression was inhibited, while p-STAT-727 expression was activated, eventually downregulating Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 99%